Robust institutions for sustainable water markets: A survey of the literature and the way forward - Alexandros Maziotis; Elisa Calliari; Jaroslav Mysiak (Fondazione Eni Enrico Mattei (FEEM), 2013)
This paper discusses a framework for analyzing robust institutions for water markets drawn on the new institutional economics school of thoughts which is based on Williamson, North, Coase and Ostrom theories on transaction cost economics, property rights and collective actions. Based on these theories, we review the evolution and development of water reforms and markets in countries such as Australia, USA (California and Colorado), Chile and in Spain. Based on the lessons learned from the Spanish and international experience on water markets, a list of robust recommendations for the improvement of water markets in Spain is proposed. These include among others, not only the definition of secure water rights, through the registration of rights or recognition of environment as a legitimate user, but also the monitoring of water trading activities, including the collection of information for prices and quantities or cost-benefit analysis for quantifying benefits and externalities. Finally, based on Sharma's approach (2012) a new robust water governance model for Spain is proposed in which the highest priority is given to the role of legal and political institutions and second priority to environmental, economic and social needs. We hope that the framework presented in this paper will function as a tool for researchers and policy makers in Spain and other European countries to understand how water markets can be further developed to be economically and environmentally efficient, and socially accepted.
Keywords: B52; D23; Q25; 330; New Institutional Economics; Robust Design Principles; Water Governance; Institutions; Water Markets